Urbanising India and river health. - Amerasinghe, Priyanie H. (2012)
The presentation looks at the current status of river systems of India from a basin perspective, and review how indicators of urbanization, such as demographics and migration, infrastructure development, growth of cities and towns, development of urban agglomerations, provision of utility services and land-use changes, have impacted the life of rivers. Further, river health in terms of water quality and quantity, biodiversity, ecological habitats, livelihood opportunities, roles and relevance of institutional structures, community-based systems for management, and resource recovery and reuse are discussed using selected case studies.